Selection of inorganic-based fertilizers in forward osmosis for water desalination - Mishra, Tripti; Srivastava, RK (International Journal of Environment, 2015)
The current study aims at the selection of an appropriate draw solute for forward osmosis process. Separation and recovery of the draw solute are the major criteria for the selection of draw solute for forward osmosis process. Therefore in this investigation six inorganic fertilizers draws solute were selected. The selections of inorganic fertilizers as draw solute eliminate the need of removal and recovery of draw solute from the final product. The final product water of forward osmosis process has direct application in agricultural as nutrient rich water for irrigation. These inorganic fertilizers were tested based on their water extraction (water flux) capacity. This experimental water flux was compared with the observed water flux. It was noted that the observed water flux is much higher than the attained experimental water flux. The difference of these two fluxes was used to calculate the performance ratio of each selected fertilizer. Highest performance ratio was shown by low molecular weight compound ammonium nitrate (22.73) and potassium chloride (21.03) at 1 M concentration, whereas diammonium phosphate (DAP) which has highest molecular weight among all the selected fertilizer show the lowest performance ratio (10.02) at 2 M concentration. DOI: http://dx.doi.org/10.3126/ije.v4i2.12660 International Journal of Environment Vol.4(2) 2015: 319-329